Dimensions of school climate at Sekolah Menengah Kebangsaan Agama (SMKA), Malaysia - Muhajir (Institute of Education, International Islamic University Malaysia, 2013)
The purpose of this study is to examine the relative influence of dimensions that have been identified to effect the school climate, as well as the influence of religiosity, in the context of national secondary religious schools where Islam plays a fundamental role. The study also aims to find out the significance of school climate dimensions as perceived by students and teachers at Sekolah Menengah Kebangsaan Agama (SMKA). Two sets of questionnaires, one for teachers and one for students, are specifically designed for data collection. A sample of 845 respondents, 279 teachers (75 male and 204 female) and 566 students (164 male and 402 female) is selected from the aforesaid schools. Rasch Measurement Model and Confirmatory Factor Analyses are conducted to answer the research questions. In addition, descriptive analyses and Mann-Whitney U-Test and Kruskal-Wallis H-Test are used in the analyses. The results indicate that for teachers, the most dominant dimension of school climate is the dimension of Social System, whereas the dimension of Culture is the most dominant for students. However, the religiosity dimension for teachers is in the third level of five-dimension of school climate, while for the students, it is in the last level. The results indicate that there is no significant difference between urban and rural schools according to teachers, while for the students, only the factor of Ecology showed significant difference. Finally, the results also indicate that the Milieu shows significant difference among students' view about the school climate based on their different streams of study, while the other dimensions such as Social System, Culture, Ecology and Religiosity show no significant difference. Implications and recommendations are stated for stakeholders.